Answer:
x³ - y³ = 0
Explanation:
Given :
![(x)/(y)+(y)/(x)=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/ylpm0g4rh2j1s2ujwjqrxkworov8y4icst.png)
To Find : value of (x³ - y³)
Since,
![(x)/(y)+(y)/(x)=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/ylpm0g4rh2j1s2ujwjqrxkworov8y4icst.png)
![(x^2+y^2)/(xy)=-1](https://img.qammunity.org/2021/formulas/mathematics/high-school/1i4oy8wc6xueuta7hxye18d0784p1550nz.png)
x² + y² = -xy
x² + y² + xy = 0 -----(1)
Since, x³ - y³ = (x - y)(x² + xy + y²) [From the formula, (a³ - b³) = (a -b)(a²+ b² + ab)
= (x - y)(0) {From equation (1)]
= 0
Therefore, value of x³ - y³ = 0 will be the answer.